Sosialisasi dan Motivasi Peserta Didik Sebagai Upaya Mempersiapkan Generasi Emas Kota Subulussalam - Shinta Riski Amanda; Asmaul Husna; Yuhdi Fahrimal; Cut Asmaul Husna (Lok Seva: Journal of Contemporary Community Service, 2023)
Education is the first step in building and forming a generation that has a constructive mindset. Education will create a golden age that can be used as a hope to change civilization. School institutions are the first place that plays a vital role in introducing the importance of higher education to students to motivate them to continue their education at a higher level. This service activity was carried out at Sultan Daulat 1 Public High School to first inform access to information on scholarships to continue their education at state universities. Second, to provide information related to the entrance route to state universities. Third, to inform about the basic terms that exist in tertiary institutions. Fourth, to help direct and introduce what study programs can be taken based on the interests and abilities of each individual who will run them. The methods used in this community service activity include (1) planning and preparation, (2) the implementation process using the lecture method, and (3) evaluation. The target group in this community service activity is students from grades 11 and 12 from the Science and Social Studies majors so that there is representation from each department to extend information to other students at the school. This activity resulted in a significant change in interest in continuing education from before socialization. There were only a few students who had an interest in continuing their education after the socialization. Some very many students wanted to continue their education.